Divided Cultures or Divided Societies? The Case of Cyprus: Раздвоени култури или раздвоени општества? Случајот на Кипар - Demosthenous, Areti (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Areti Demosthenous | Арети Демостенус Title (English): Divided Cultures or Divided Societies? The Case of Cyprus Title (Macedonian): Раздвоени култури или раздвоени општества? Случајот на Кипар Translated by (English to Macedonian): no record Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 165-184 Page Count: 19 Citation (English): Areti Demosthenous, “Divided Cultures or Divided Societies? The Case of Cyprus,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007): 165-184. Citation (Macedonian): Арети Демостенус, „Раздвоени култури или раздвоени општества? Случајот на Кипар“, Идентитети: списание за политика, род и култура, т. 6, бр. 1 (зима 2007): 165-184.